2014
DOI: 10.15640/jmm.v2n3-4a4
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Consumption Model for Malaysian Consumers

Abstract: The objective of this research is to construct a consumption model for Malaysian consumers. The research is important for Malaysian national agenda, especially, in achieving a societal integrity, social cohesion, the vision of 2020, and developed country per capita income, with the slogan of "1 Malaysia, People First, Performance Now". The consumption pattern of Malaysian consumers has changed markedly since 2005 as shown by several indicators such as consumer price index (CPI), per capita income and inflation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…More specifically, consumers` healthy lifestyle underlies the relationship between promotion and consumption patterns. The result is consistent with past studies that found mediation of healthy lifestyle role (Blackwell et al, 2006;Hawkinks et al, 1998;Sulaiman., 2014).…”
Section: The Mediating Effect Of Consumer Healthy Lifestyle On the Relationship Between Promotion And Consumption Patterns Of Healthy Foosupporting
confidence: 93%
See 3 more Smart Citations
“…More specifically, consumers` healthy lifestyle underlies the relationship between promotion and consumption patterns. The result is consistent with past studies that found mediation of healthy lifestyle role (Blackwell et al, 2006;Hawkinks et al, 1998;Sulaiman., 2014).…”
Section: The Mediating Effect Of Consumer Healthy Lifestyle On the Relationship Between Promotion And Consumption Patterns Of Healthy Foosupporting
confidence: 93%
“…The mediation effect of consumer healthy lifestyle on promotion and consumption patterns has been rarely discussed in past empirical research in healthy food ( Blackwell et al 2006;Hawkins et al 1998;Sulaiman et al 2014). Under-review study conducted by Sulaiman et al(2014), tested the mediation effect on consumer lifestyle in the link between promotion and consumption patterns among Malaysian consumers. Similarly, Hawkins et al (1998), proposed a conceptual model to test the intervening variable of consumer lifestyle between promotion under marketing activities towards consumer decision process by referring to consumption patterns.…”
Section: Consumers` Healthy Lifestyle Mediates Between Promotion and Consumption Patterns Of Healthy Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Yaty Sulaiman et al (2014), the Malaysian consumer consumption pattern has changed significantly since 2005 through several indicators such as the Consumer Price Index (CPI), per capita income and inflation rate. The increase in consumer price index (CPI) from 95.4% in 2000 to 122.8% in 2013 indicates that consumers have to pay higher prices for consumer goods due to rising commodity prices such as oil palm, rubber and fuel prices.…”
Section: Introductionmentioning
confidence: 99%